A note on Second Degrees in Graphs - Naji, Ahmed Mohammed (Indonesian Combinatorial Society (InaCombS), 2023)
The second degree of a node x in a graph Γ=(V,E), denoted by deg2(x), is the number of nodes at distance two from x in a graph Γ. In the present article, we are interested in examination of the second degrees properties in a graph. The old bounds and the general formulas of the second degree of some graph operations are collected. We provide an improvement on the useful result